A study of Singapore’s off-peak car (OPC) scheme the authority’s perspective - Muhammad Saifulbahry Abdul Raman. (2012)
In 1991, the Weekend Car (WEC) scheme was introduced to manage the demand of car ownership. The objective of the scheme was to allow for a higher ownership of cars at a lower cost without contributing to traffic congestion during normal economic hours. The scheme has since undergone many modifications and is now known as the revised Off-Peak Car (OPC) scheme.